Engel curves, spatial variation in prices and demand for commodities in Côte d'Ivoire - Monnet Benoit Patrick Gbakou; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2011)
This paper aims to estimate the price and income elasticities of the demand for essential commodities in Cote d'Ivoire. Using data from the 2002 Cote d'Ivoire Living Standard Survey and a theoretical framework developed by Crawford et al. (2003), we analyse price effects on the demand for groups of commodities by exploiting a relationship between unit values and commodity quantities and deriving Engel curves. Our findings reveal that the own-price elasticity of meat and dairy products is considerably stronger for rich households (those in the 90th percentile of total expenditure) than for poor households (those in the 10th percentile of total expenditure). Although all the modelled groups of commodities are normal goods, the paper shows that starch is more of a necessity for poor households than for rich ones, whereas meat and dairy products are more of a luxury good for poor households than for rich households.
urn:nbn:de:101:1-201104133732
Keywords: D11; D12; 330; consumer demand; unit values; developing country; Nahrungsmittelkonsum; Mikroökonomische Konsumfunktion; Lebensstandard; Elfenbeinküste